2009
DOI: 10.1111/j.1365-2850.2008.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

University students' suicidal thoughts and influencing factors

Abstract: This research was planned as a descriptive study for the purpose of examining the suicidal thoughts of first-year university students and the factors that might affect them. The research was conducted with the participation of first-year students (class of 1992) at Ege University between January 2003 and October 2004. The research data were collected on a form prepared by the researcher to determine the university students' socio-demographic characteristics and their suicidal thoughts, the trait anger, express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 64 publications
(51 reference statements)
4
15
0
4
Order By: Relevance
“…Lee et al (23) showed that anger is an important marker for people, who may be at risk of engaging in suicidal behavior. A similar finding was also reported in a Turkish study (24), in which suppressed anger was shown to increase suicidal thoughts. In the present study, intense feelings and tendency to suppress anger might increase suicidal thought.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lee et al (23) showed that anger is an important marker for people, who may be at risk of engaging in suicidal behavior. A similar finding was also reported in a Turkish study (24), in which suppressed anger was shown to increase suicidal thoughts. In the present study, intense feelings and tendency to suppress anger might increase suicidal thought.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have demonstrated possible relationships between higher anger and suicidality (23, 24). The present study increases our knowledge about the relationship between anger and suicide idea.…”
Section: Discussionmentioning
confidence: 97%
“…However this factor appeared to be in fact somewhat protective against actual suicidal action in our sample. This is congruent with its negative correlation with BSI depression scores, but contrasts with much literature examining somatization [43][45], dissociation [46], and suicidality in at risk patient populations., It is consistent with the findings of others, however [47], [48], as well as findings for individual items on the STS-2 [8].…”
Section: Discussionsupporting
confidence: 54%
“…Risk and protective factors play a critical role in suicide prevention and identifying risk, and protective factors provide critical information to assess and manage suicide risk in individuals. Socio‐demographic factors such as non‐heterosexual orientation, female gender, low socio‐economic status, first year of college, marital status, family relationships, adolescence, among others, have been found to be associated with increased odds and/or risk factors of suicidal behaviour (Aranmolate, Bogan, Hoard, & Mawson, ; Engin, Gurkan, Dulgerler, & Arabaci, ; Eshun, ; Fox et al, ; Hawton, Saunders, & O'Connor, ; Mortier, Auerbach, Alonso, Axinn et al, ; Mortier, Auerbach, Alonso, Bantjes et al, ; Mortier, Cuijpers et al, ; Mortier et al, ,; Tyssen, Vaglum, Grønvold, & Ekeberg, ). Some studies have shown religious involvement, being married and having supportive social connections (Colucci & Martin, ; Gearing & Alonzo, ; Milner et al, ) to be associated with reduced odds of suicidal behaviour and/or as protective factors against suicide ideation and attempts.…”
Section: Introductionmentioning
confidence: 99%